PENGAWASAN BADAN PERMUSYAWARATAN DESA TERHADAP PELAKSANAAN PERATURAN DESA TENTANG ANGGARAN PENDAPATAN DAN BELANJA DESA DIDESA BANDUR PICAK KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR TAHUN 2012 - Lusi Fitrianti; Auradian Marta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Supervision is very important in all work, what else in the government, lack of supervision is a phenomenon that is polemical and losses for various parties, this phenomenon also occurred in the village of Bandur picak Koto Kampar District of Hulu Kampar, where BPD Monitoring of Implementation Regulation of the Village About APBDes less maximum due to the realization of village finances has not been running well and there are many community organizations that have not received funding because the funding provided is not sufficient. The authors wanted to examine further on the Control of Village Consultative Body of Implementation Regulation of the Village About Budget village Village In the village of Koto Kampar District of Bandur picak Hulu Kampar Regency in 2012.The purpose of this study was to determine the performance of BPD in carrying out surveillance of Village Regulations About APBDes and determine the factors inhibiting the performance of BPD. The method used is descriptive qualitative. Informants in this study is the Head Koto Kampar Hulu, picak Bandur village chief, village secretary, BPD Chairman, Vice-Chairman of the BPD, Desa Bandur picak Kaur, Chief LPM, Kadus, Ninik Mamak and picak Bandur Village Society, the Data Collection Techniques Interviews to find out the extent to which the BPD Supervision Regulations village, qualitative data analysis technique that is performed on the data, in this case the qualitative data in the form of information, a description in the form of prose language other then associated with the data to gain clarity on the truth.Results from this study, the Village Consultative Monitoring Regulatory Agency Village About Budget Village in the Village Bandur picak already implemented properly and in accordance with existing regulations, only lack of education BPD, BPD lack of understanding of the duties and functions, lack of facilities and lack of Inhibiting factors form the village fund BPD in carrying out their duties, as well as other factors, such as mental attitude, and indigenous factors / kinship that exist.Keywords: Monitoring, BPD, Village Regulati